Impression management strategies and water disclosures – the case of CDP A-list - Fialho, Ana (2021)
Purpose The purpose of this paper is to investigate whether the introduction of water security, in 2015, as a category in the Carbon Disclosure Project (CDP) Climate A-List, increases the use of impression management (IM) strategies. The purpose is to analyze how companies reacted to programmes of voluntary disclosure of environmental information. Design/methodology/approach Mixed-methods research was developed, combining a qualitative and quantitative approach. This study first used a qualitative content analysis of 15 companies’ reports, from the materials sector, which was scored in the CDP Climate A-List, in 2017, to identify the IM strategies adopted. Next, this study conducted a quantitative analysis to test the mean differences of water references between years, industry and region. Findings Three types of IM strategies are identified (justification and commitment, self-promotion and authorization). The references identified as self-promotion strategy increased in 2016. This indicates companies reacted to the programmes for voluntary disclosure of environmental information by increasing strategies of legitimization and image promotion. Research limitations/implications Further research can be developed, focusing only on sustainability reports and extending the number of companies, the period and sectors under analysis. Originality/value This paper shows how the inclusion of a topic such as water security in an environmental ranking of companies, namely, CDP A-List, affects the use of IM strategies in voluntary disclosures